HUBUNGAN MOTIVASI BELAJAR DAN SELF-REGULATED LEARNING DENGAN HASIL BELAJAR FISIKA SISWA KELAS XI SMA NEGERI 4 PEKANBARU TAHUN PELAJARAN 2016/ 2017 - Sartika Noviyanti Br Simatupang; Nur Islami; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the correlation learning motivation and self-regulated learning with physics learning result of class XI SMA Negeri 4 students Pekanbaru. Type of this research is correlational research. The sample in this study amounted to 64 students of class XI IPA SMA Negeri 4 Pekanbaru. The of research instrument used questionnaires and documentation. Data analysis technique us correlation product moment and multiple correlation. The result of the research shows that: (1) there is a positive correlation between learning motivation (X1) with the learning result of physics (Y) which is proved rx1y = 0.465, Rx1y = 0.216, tcount = 4.136, (2) there is a positive correlation between self- regulated learning (X2) with the result of physics (Y) which is proved rx2y = 0.448, Rx2y = 0.201, tcount = 3.394, (3) there is a positive correlation between learning motivation (X1) and self-regulated learning (X2) with the learning result of physics (Y) which is proved rx1x2y = 0.553, Rx1x2y = 0.305, Fcount = 13.407. This study concludes that high learning motivation and self-regulated learning can improve physics learning outcomes.Keywords: Learning Motivation, Self-Regulated Learning, Learning Result